Online learning: satisfaction of university students with work experience - Vásquez-Pajuelo, Lida (2020)
This research review presents the results of the analysis, an explanation and an application of the concept of satisfaction for online learning in a university degree program developed for people with work experience. It is a univariable descriptive study, based on a mixed, intersubjective approach, type, carried out with data collection through surveys and virtual interviews. The Blackboard Learn platform is used, which is the actual virtual environment for learning. The information gathering instruments are applied, using the aforementioned technological means, on the 801 students of the year 2014, majoring in International Business, Marketing and Commercial management, Business Administration and Accounting. The results obtained indicate that the study variable, satisfaction with online learning, has been validated for the "University Programs for People with Work Experience" (CPEL, in Spanish), based on the application of a practical methodology for its measurement.